Maternal iodine status in a multi‐ethnic UK birth cohort: Associations with child cognitive and educational development. Issue 2 (1st September 2020) - Threapleton, Diane E.; Snart, Charles J. P.; Keeble, Claire; Waterman, Amanda H.; Taylor, Elizabeth; Mason, Dan; Reid, Stephen; Azad, Rafaq; Hill, Liam J. B.; Meadows, Sarah; McKillion, Amanda; Alwan, Nisreen A.; et al.
Abstract: Background: Maternal iodine requirements increase during pregnancy to supply thyroid hormones critical for fetal neurodevelopment. Iodine insufficiency may result in poorer cognitive or child educational outcomes but current evidence is sparse and inconsistent. Objectives: To quantify the association between maternal iodine status and child educational outcomes. Methods: Urinary iodine concentrations (UIC) and iodine/creatinine ratios (I:Cr) were measured in 6971 mothers at 26‐28 weeks' gestation participating in the Born in Bradford cohort. Maternal iodine status was examined in relation to child school achievement (early years foundation stage (EYFS), phonics, and Key Stage 1 (KS1)), other learning outcomes, social and behavioural difficulties, and sensorimotor control in 5745 children aged 4‐7 years. Results: Median (interquartile range) UIC was 76 µg/L (46, 120), and I:Cr was 83 µg/g (59, 121). Overall, there was no strong or consistent evidence to support associations between UIC or I:Cr and neurodevelopmental outcomes. For instance, predicted EYFS and phonics scores (primary outcomes) at the 25th vs 75th I:Cr percentiles (99% confidence intervals) were similar, with no evidence of associations: EYFS scores were 32 (99% CI 31, 33) and 33 (99% CI 32, 34), and phonics scores were 34 (99% CI 33, 35) and 35 (99% CI 34, 36), respectively. Conclusions: In the largest single study of its kind, there was little evidence of detrimental neurodevelopmental outcomes in children born to pregnant women with iodine insufficiency as defined by World Health Organization–outlined thresholds. Alternative functional biomarkers for iodine status in pregnancy and focused assessment of other health outcomes may provide additional insight.